Zakat and Sustainable Development: A Macroeconomic Analysis of Poverty, Inequality, and Growth in Indonesia - Delima Sari Lubis; Andri Soemitra; Isnaini Harahap (Lan Tabur: JURNAL EKONOMI SYARIAH, 2026)
This study examines the dynamic relationship between zakat distribution, poverty depth, income inequality, and economic growth in Indonesia within the framework of sustainable development. Using semiannual data from the first semester of 2011 to the first semester of 2025, the analysis applies a Vector Error Correction Model (VECM) to capture both long-run equilibrium relationships and short-run dynamics among the variables. Poverty is measured using the Poverty Gap Index (P1), which reflects the depth and severity of poverty rather than merely its incidence. The results confirm the existence of a stable long-run cointegration relationship between zakat, poverty depth, income inequality, and economic growth. In the long run, zakat distribution shows a significant negative elasticity of −0.842, indicating that a 1% increase in zakat distribution reduces poverty depth by approximately 0.84%. Income inequality exerts the strongest structural influence with a positive elasticity of 1.915, while economic growth reduces poverty with a smaller elasticity of −0.276. The error correction term (−0.431) indicates relatively rapid adjustment toward long-run equilibrium, with about 43% of short-run disequilibrium corrected within one semester. Impulse response and variance decomposition analyses further reveal that zakat contributes meaningfully to medium- and long-term poverty dynamics. These findings suggest that zakat functions as a redistributive stabilizer embedded within the macroeconomic system, complementing economic growth and mitigating inequality. This study does not account for informal zakat flows, which may imply that the estimated macro effect is conservative. Overall, the study provides empirical support for integrating Islamic social finance into national sustainable development strategies aimed at poverty reduction and inclusive growth.